2013
DOI: 10.1002/smj.2193
|View full text |Cite
|
Sign up to set email alerts
|

Capabilities as shift parameters for the outsourcing decision

Abstract: In this paper, we argue that capabilities serve as shift parameters that result in a change in the critical value of asset specificity at which firms switch from in-sourcing to outsourcing. Capabilities have two effects: they result in a change in firm production costs and in firm governance costs relative to the market. As a result, the frontier at which market governance gives way to firm governance shifts. Three factors that produce such shifts are the value, rarity, and inimitability of capabilities employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…External production cost advantage is the degree to which a provider is perceived to have an advantage over a client organization in production cost economies (e.g., Williamson, 1991;Rajeev and Vani, 2009). TCE suggests that the market's external production cost advantage should be positively associated with outsourcing decisions, and indeed four out of five empirical tests found that relationship (e.g., Dibbern et al, 2012;Freytag et al, 2012;Jain and Thietart, 2014). One study found that external production cost advantage was negatively associated with IT-shared services (Gefen et al, 2011), which was also a consistent finding with TCE.…”
Section: Transaction Attributesmentioning
confidence: 64%
See 1 more Smart Citation
“…External production cost advantage is the degree to which a provider is perceived to have an advantage over a client organization in production cost economies (e.g., Williamson, 1991;Rajeev and Vani, 2009). TCE suggests that the market's external production cost advantage should be positively associated with outsourcing decisions, and indeed four out of five empirical tests found that relationship (e.g., Dibbern et al, 2012;Freytag et al, 2012;Jain and Thietart, 2014). One study found that external production cost advantage was negatively associated with IT-shared services (Gefen et al, 2011), which was also a consistent finding with TCE.…”
Section: Transaction Attributesmentioning
confidence: 64%
“…Service complexity is the degree to which a service or project requires compound steps, the control of many variables, and/or where cause and effect are subtle and dynamic (e.g., Ventovuori and Lehtonen, 2006;Penfold, 2009). Among six empirical examinations, we coded five negative relationships between service complexity and outsourcing (e.g., Jain and Thietart, 2014), offshoring (e.g., Poston et al, 2010), and degree of outsourcing (e.g., Aubert et al, 2012). One study found no discernable relationship (Susarla et al, 2010b).…”
Section: Transaction Attributesmentioning
confidence: 99%
“…The examination of the effects of outsourcing process mechanisms on insourcing is 12 Major differences in datasets, analytical methods, and study contexts forbid a true comparison of Jain and Thietart's (2013) findings with those of this study. Jain and Thietart's study is cross-sectional and focuses on the role of production and governance costs on outsourcing decisions; our study is longitudinal and focuses on the role of outsourcing process on insourcing decisions.…”
Section: Implications For Research On Private and Public Servicesmentioning
confidence: 87%
“…On the other hand, our theory and findings provide further evidence that the strategic decision process in local governments is different to that in the private context. For instance, in a study of IS sourcing decisions Jain and Thietart (2013) found that capabilities associated with organizational processes decrease the likelihood of outsourcing. 12 Future research should further probe the application of concepts and methodologies from the private to the public context, and vice versa.…”
Section: Implications For Research On Private and Public Servicesmentioning
confidence: 99%
“…First, in general, pooling of whole organizations via merger does not favor the fast and selective targeting of which assets or activities to pool for maximum gain (Hennart & Reddy, 1997;Reuer & Koza, 2000). Second, outsourcing to a party that generates efficiencies by pooling multiple clients' business can be attractive, but entails a loss of autonomy and competence (Jain & Thietart, 2014). Implementing a scale alliance requires making choices about capacity reduction, shifting and addition throughout the lifespan of the alliance.…”
Section: Background: Value In Public Organizations and Decision-makingmentioning
confidence: 99%